Bobabox SME Development Strategy Based on the Influence of Supply Chain Resilience Variables on Company Performance - Dhede Pristi Afrinda; Nazaruddin Matondang; Juliza Hidayati (Jurnal Sistem Teknik Industri, 2025)
Supply chain resilience refers to the capacity of a supply chain to develop adequate responsiveness, readiness, and recovery strength so it can handle risks and disruptions and restore its operations to their previous condition or achieve an even better state. Bobabox faced challenges such as fluctuating sales, the closure of six outlets, shifting customer demand, and increasing competition. This study involved 81 boba drink outlets in Medan using purposive sampling. Data were collected through questionnaires and an interview with the Bobabox CEO, then analyzed using Smart-PLS 4 to test relationships between variables. SWOT and QSPM methods were applied to formulate strategies. The findings show that supply chain resilience significantly influences company performance. The IE matrix placed Bobabox in quadrant V (hold and maintain), suggesting that the company should preserve its current market position and focus on efficiency rather than aggressive expansion. The study identified 11 internal factors (IFE score: 2.73636) and 8 external factors (EFE score: 2.67857). The SWOT matrix produced nine alternative marketing strategies. Based on the QSPM results, the most recommended strategy is reducing supplier dependency through multi-sourcing to mitigate geopolitical risks (W2, T3).